Peran Muhammadiyah dan Nahdlatul Ulama dalam Problematika Kerusakan Lingkungan Hidup di Indonesia - Fauzanto, Adi (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Sekolah Tinggi Islam Blambangan (STIB) Banyuwangi, 2020)
The outline of environmental problems is divided into two, namely environmental pollution and environmental damage. These problems, both pollution and damage, certainly need to be overcome to realize sustainable development. There are four principles for realizing sustainable development, one of which is the opportunity for self-determination which includes community participation in a democratic system. Community participation must have a forum to accommodate aspirations that are not oriented to the interests of power, and economic interests, such institutions are community organizations. As Islamic community organizations in Indonesia, namely Muhammadiyah and Nahdlatul Ulama. This study uses a qualitative data comparison approach between the two research objects and produces descriptive data relating to the role and methods of the Muhammadiyah and Nahdlatul Ulama organizations in the problem of pollution and environmental damage in Indonesia. The results and discussion are both having roles and methods in dealing with environmental pollution and damage in the fields of law, education, advocacy, and literacy